Nexus between government debt, economic policy uncertainty, government spending, and governmental effectiveness in BRIC nations: Evidence for linear and nonlinear assessments - Ma, Ru; Qamruzzaman, Md (Frontiers in Environmental Science, 2022)
Quality institutions augmented the sustainability of the economy and ensured domestic resources optimization for equitable development. Therefore, ensuring the equitable development of quality institutions is inevitable. The motivation of the study is to gauge the role of government debt, economic policy uncertainty, and government spending on institutional quality, which is measured by governmental effectiveness in BRIC (Brazil, Russia, India, and China) nations for the period 1990-2020. The study employed Augmented ARDL, nonlinear ARD,L and Fourier Toda-Yamamoto causality test in exploring the empirical relationships. Study documented long-run cointegration in both symmetry and asymmetric assessment. In the long run, both government debt and economic policy uncertainty revealed a negative and statistically significant association with institutional quality, while a positive linkage was established between government spending and institutional quality. Furthermore, asymmetric ARDL unveiled both long-run and short-run asymmetric relationships between institutional quality and government debt, E,PU and government spending. The directional causality test documented bidirectional causality between debt and institutional quality in all nations, whereas mixed causalities were detected for economic policy uncertainty, institutional quality, and government spending.